PERBANDINGAN NILAI PERCEPATAN TANAH MAKSIMUM BERDASARKAN MODIFIKASI KONSTANTA ATENUASI DAN DATA ACCELEROGRAPH TAHUN 2008-2016 PADA STASIUN BMKG LAMPUNG - Pipit Melinda Meitawati; Bagus Sapto Mulyatno; Karyanto Karyanto; Agung Setiadi (Engineering Faculty Universitas Lampung, 2018)
Peak ground acceleration is one of the parameters used in estimating the extent of breakdown caused by earthquake shocks. In the present study, the determination of an attenuation empirical formula PGA (Peak Ground Acceleration) based on the attenuation equation Lin and Wu (2010). Data used in the study of seismic event data by period year 2008-2012. Through the calculation of regression analysis, then obtained the function attenuation of peak ground acceleration in Lampung region at each station accelerograph.At the LWLI accelerograph station obtained the value of the empirical coefficient of the distance of earthquake -2.351, the empirical coefficient of earthquake magnitude 0,574, and the constant 2,430. At the KASI accelerograph station obtained the value of the empirical coefficient of the distance of earthquake -2.522, the empirical coefficient of earthquake magnitude 0.654, and the constant 2.182. At the BLSI accelerograph station obtained the value of the empirical coefficient from the distance of earthquake -3.224, the empirical coefficient of earthquake magnitude 0.651, and constant 4,092. At the KLI accelerograph station obtained the value of the empirical coefficient from the distance of earthquake -2.746, the empirical coefficient of earthquake magnitude 0.751, and the constant 2.053.Result of correlation test verification, chart relation between distance and magnitude earthquakes, ratio PGA contour maps, as well as a ratio between the value of PGA models with the observation of accelerograph year 2013-2016 show that the acceleration attenuation function of the obtained soil is relatively good. Based on PGA attenuation contour map model at an event the earthquake on 28th May 2011, PGA great value be found in the Liwa region with a PGA score of 10-20 gal and its seismic intensity value is V-VI MMI. It happens because of the source the earthquake is in the western sea of Liwa.